Comparison between the fatigue response of hot and warm mix asphalts based on the dissipated energy approach. Issue Volume 18:Issued 1(2017) (2nd January 2017) - Modarres, Amir; Aloogar, Ashkan
Abstract : This study focused on the fatigue behaviour of warm mix asphalt (WMA) based on the dissipated energy (DE) approach. Two conventional binders consisting of 60/70 and 85/100 penetration-grade bitumens were used to prepare the control mix. WMA was prepared by incorporating 2% Sasobit by weight of bitumen. First, the basic properties of WMA containing optimum bitumen content were compared with those of control hot mix asphalt (HMA). The main laboratory programme included four-point flexural fatigue test that was accomplished at different strain levels of 250, 500, 750 and 1000 microstrain. The studied WMA had comparable Marshall stability and indirect tensile strength to those of control HMA. Furthermore, based on the resilient modulus test results, the temperature susceptibility of WMA was slightly more than that of the control mix. Fatigue lives of studied mixes were evaluated using the conventional fatigue curves that were developed based on the initial strain level. Comparison between these curves revealed the predominant fatigue behaviour of WMAs at different examined strain levels. The initial DE and the cumulative DE of WMAs were lower than those of HMAs. The latter issue justifies the predominant fatigue response of WMA. By considering the DE curve, the ratio of dissipated energy change (RDEC) was calculated. Afterward, the plateau value (PV) was determined using the moving average of fatigue data in the plateau stage of the RDEC curve. Finally, PV-based fatigue models were developed which could precisely estimate the fatigue life regardless of the mix type and testing condition.